Uma revisão da literatura sobre Pseudomonas aeruginosa: fatores de virulência e resistência bacteriana - Lima, Maria Letícia Xavier de (2022)
Pseudomonas aeruginosa is a pathogenic bacterium, widely distributed in nature and in the hospital environment, commonly involved in nosocomial infections, infections in immunocompromised and chronic infections, especially in patients with cystic fibrosis. It is characterized by having several virulence factors and resistance mechanisms that can make it difficult to treat infections. In view of this, the objective of the present work is to carry out a review of the literature on the virulence factors and bacterial resistance of Pseudomonas aeruginosa. In this way, a wide search was carried out for scientific articles, published in PubMed, Scientific Electronic Library Online (SciELO), Google Scholar, Lilacs and Medline, which were in accordance with the proposed subject. The research covered the period from 2018 to 2020. With this, it was realized that Pseudomonas aeruginosa is an important opportunistic pathogen, causing infections that are difficult to treat, due to its resistance to several antimicrobials, resulting in increased morbidity, mortality and costs. Therefore, due to antimicrobial resistance being an increasingly present problem, the development of new therapeutic options is urgently essential, as well as the consolidation of strategies for the prevention and control of infections, in hospital institutions. In addition to carrying out awareness campaigns, aimed at the population, aiming to mitigate the excessive and irrational use of antimicrobials.